2001
DOI: 10.1074/jbc.m010879200
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Erythrocyte Ghosts That Determine Susceptibility to Secretory Phospholipase A2

Abstract: Artificial membranes may be resistant or susceptible to catalytic attack by secretory phospholipase A 2 (sPLA 2 ) depending on the physical properties of the membrane. Living cells are normally resistant but become susceptible during trauma, apoptosis, and/or a significant elevation of intracellular calcium. Intact erythrocytes and ghosts were studied to determine whether the principles learned from artificial systems apply to biological membranes. Membrane properties such as phospholipid and/or protein compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 54 publications
4
71
1
Order By: Relevance
“…The two-photon excitation images were collected on an Axiovert 35 inverted microscope (Zeiss, Thornwood, NY) at the Laboratory for Fluorescence Dynamics (Urbana, Il) as described previously (12,13,21). The excitation source was a titanium-sapphire laser (Coherent, Palo Alto, CA) tuned to 780 nm and pumped by a FIGURE 1: Effects of temperature on fluorescence emission of laurdan in erythrocytes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-photon excitation images were collected on an Axiovert 35 inverted microscope (Zeiss, Thornwood, NY) at the Laboratory for Fluorescence Dynamics (Urbana, Il) as described previously (12,13,21). The excitation source was a titanium-sapphire laser (Coherent, Palo Alto, CA) tuned to 780 nm and pumped by a FIGURE 1: Effects of temperature on fluorescence emission of laurdan in erythrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, it was observed that erythrocytes normally resist the action of sPLA 2 , but that upon the addition of a calcium ionophore such as ionomycin, they become susceptible (12). This increase in susceptibility appears to be linked to an accompanying increase in the order of membrane lipids (12,13). Nevertheless, one question that remained unresolved was whether the critical issue for increased susceptibility was the average level of membrane order or the spatial distribution of membrane regions of differential order.…”
mentioning
confidence: 99%
“…Two-photon laurdan images were obtained at the Laboratory for Fluorescence Dynamics (University of California, Irvine) as described previously (20,21). Laser emission was 780 or 790 nm (depending on laser stability and performance each day).…”
Section: Two-photon Scanning Microscopymentioning
confidence: 99%
“…10, 11) could be the fact that intracellular hemoglobin may quench the fluorescence of DPH and laurdan in the inner leaflet through energy transfer (49). Moreover, optical absorbance of emitted light by hemoglobin also alters the measured value of laurdan GP (20). Means to correct for these phenomena have been published (20,50).…”
Section: Erythrocytesmentioning
confidence: 99%
“…Laurdan in the lipid phase shows spectral sensitivity with a red shift of the emission maximum when passing from a gel to a liquid crystalline phase (Chong and Wong, 1993;Parasassi et al, 1990;Parasassi et al, 1991;Sheffield et al, 1995). Based on this property, laurdan has been used to estimate the fluidity of the membrane in various living cells (Chapman et al, 1995;Harris et al, 2001;Mamdouh et al, 1998;Palleschi and Silvestroni, 1996;Sasaki et al, 2006;Vest et al, 2004;Yu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%